Comparison between Hiding in Corners Regions and Hiding in Regions between Corners by using Characteristic Regions of FAST Corner Detection - عبدالله كريم, Dr.Abdulameer; فالح ناصر, Ekhlas (مجلة كلية التربية, 2020)
The invisible science of communication is called steganography. It employs various useful applications. Hiding of information change almost whole cover image for most techniques of steganography that perhaps affect negatively the visual quality of an image and raise the potential of hidden data losing after the potential attacks. This research offers a novel technique for steganography based on hiding between corners regions to solve this problem, which was hiding data in the robust regions of an image. The approach has been employed to discover the robust image regions between corners which are resulted by employing features from accelerated segment test (FAST) method. The outcomes displayed that the accuracy of hiding data between corners regions is higher for retrieving an embedded data and that the visual embedded image quality than embedded data into corners regions themselves.